An indirect model reference adaptive control algorithm based on multidetected-output controllers - Arvanitis, Kostas G. (Zielona Góra: Uniwersytet Zielonogórski)
The use of sampled-data multidetected-output controllers for model reference adaptive control of linear systems with unknown parameters is investigated. Multidetected-output controllers contain a sampling mechanism in which the system output is detected many times over one period.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka